Instructor's manual for Introduction to Schenkerian analysis - Forte, Allen; Gilbert, Steven E. (New York W.W. Norton & Company, 1982)
Beginning in Part Two ideas that are more specifically Schenkerian are developed and applied to the analysis of short compositions. Since the book is also intended to cover all of the basic standard form it has seemed logical to use this feature in organizing the material. Thus, Part Two ends with longer forms and Part Three covers the main large forms (sonata, rondo, and so on). The various types of Schenkerian prolongations are introduced gradually and discussed and illustrated thoroughly in the text.Each chapter ends with a set of exercises keyed to the topics that have been presented, and the student is given precise instructions for completing the exercises as well as occasional hints about pitfalls and special problems that they contain.